2015
DOI: 10.3109/02713683.2015.1068816
|View full text |Cite
|
Sign up to set email alerts
|

Increase of SialylatedN-Glycansin Eyes with Neovascular Glaucoma Secondary to Proliferative Diabetic Retinopathy

Abstract: Our data demonstrate the distinct changes of N-glycan profile and the increase of sialylated N-glycans in eyes with NVG secondary to PDR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
3
9
0
Order By: Relevance
“…However, previous studies of N-glycosylation in 562 people with type 2 diabetes reported reduced levels of certain monogalactosylated N-glycans (NG1 [6]A2F, equivalent to GP6 in our study) in people with type 2 diabetes compared with controls (18); this is consistent with the association of lower GP6 with higher HbA 1c found in our study. Another small study of 17 people with diabetes and controls found increased sialylated N-glycans in the vitreous fluid of people with proliferative retinopathy (19). A study of one specific glycoprotein, a1acid glycoprotein, in type 1 diabetes reported altered fucosylation (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies of N-glycosylation in 562 people with type 2 diabetes reported reduced levels of certain monogalactosylated N-glycans (NG1 [6]A2F, equivalent to GP6 in our study) in people with type 2 diabetes compared with controls (18); this is consistent with the association of lower GP6 with higher HbA 1c found in our study. Another small study of 17 people with diabetes and controls found increased sialylated N-glycans in the vitreous fluid of people with proliferative retinopathy (19). A study of one specific glycoprotein, a1acid glycoprotein, in type 1 diabetes reported altered fucosylation (20).…”
Section: Discussionmentioning
confidence: 99%
“…Internal standard (IS, A2amide, 110 pmole) was added according to the standard protocol [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The rest followed the same pretreatment as human brain tissue mentioned above.…”
Section: N-glycans From Glycoproteins Of Human Brain Tissuementioning
confidence: 99%
“…By applying the general glycoblotting protocol for the human serum glycomics [13][14][15][16][17][18][19][20][21][22][23][24], we identified 52 N-glycans that can be used for further comparative study between AD patient and normal control group ( Table 2). The total expression levels of the serum N-glycans seemed to increase significantly in AD patients when compared with the normal control groups (p < 0.001 in male; p < 0.05 in female, Table 4).…”
Section: Human Ad Serum N-glycomicsmentioning
confidence: 99%
See 2 more Smart Citations